Analisis Perlakuan Akuntansi Pembiayaan Qordhul Hasan Berdasarkan PSAK No. 59 dan PSAK No. 101 - Nazilatul Hidayah; Nawirah Nawirah (Jurnal Ekonomi Akuntansi dan Manajemen, 2020)
The accounting treatment of Qardhul Hasan financing has been regulated in PSAK No. 59 and PSAK No. 101, but there are still many sharia entities especially in Baitul Maal wa Ta'lim who have not followed the Statement of Financial Accounting Standards (PSAK) rules. As well as the implementation of Qardhul Hasan financing at BMT XX which having some problems that the rate of return and funds managed are not presented in detail. Therefore, the accounting treatment of Qardhul Hasan financing at BMT XX needs to be considered. The aims of this study are to describe and adjust the accounting treatment of Qardhul Hasan financing at BMT XX with PSAK No. 59 and PSAK No. 101. This study uses a qualitative method with a descriptive approach by describing the implementation of Qardhul Hasan financing at BMT Maslahah Capem Pakisaji, then analyzing the suitability of accounting treatment in the form of recognition, measurement, presentation and disclosure of Qardhul Hasan financing at BMT XX through interviews, observation and documentation with PSAK No. 59 and PSAK No. 101. The result of this study indicates that the accounting treatment of Qardhul Hasan financing at BMT XX is not fully in accordance with PSAK No. 59 and PSAK No. 101, in terms of recognition, measurement, presentation, and disclosure of financial statements. Keywords: Accounting Treatment, Qardhul Hasan Financing, BMT, PSAK No. 59, PSAK No. 101.